Komptensi Guru Pendidikan Agama Islam Non Pendidikan Luar Biasa (PLB) di SLB X Kota Bandung - Viny Apriyantie; Erhamwilda; Enoh Nuroni (UNISBA Press, 2024)
Abstract. Ideally, teachers in SLB have a special education background to be able to perform their duties and roles in achieving learning objectives. However, the reality in the field is often different. Many of the teachers who teach in SLB come from non-Developmental Education backgrounds, one of which is the PAI teacher at SLB X Bandung City who is also an individual with low vision. Teachers who do not have a special education background usually have limited theoretical and practical knowledge related to children with disabilities. The purpose of this study was to determine the competencies possessed by non PLB PAI teachers who teach at SLB X in Bandung City. The research used descriptive qualitative methods, with data collection tools in the form of interviews, observation, and documentation. The data sources in this study came from key informants, namely the vice principal of SLB X in the field of curriculum, SLB X students, one of the teachers who taught at SLB X, while the core informants were PAI teachers of SLB X Bandung City. Based on the results of the research, although the PAI teacher does not have a PLB background, the teacher can still teach PAI to children with disabilities because of the teacher's condition who is also an individual with low vision, the personal condition also affects the teacher's success in teaching because the teacher can apply his experience and understanding to students who face similar obstacles. However, in terms of theories related to special education, teachers still have limitations. Abstrak. Idealnya, guru di SLB memiliki latar belakang pendidikan luar biasa untuk dapat melakukan tugas dan peran dalam mencapai tujuan pembelajaran. Namun, kenyataan di lapangan seringkali berbeda. Banyak guru yang mengajar di SLB berasal dari latar belakang pendidikan non PLB, salah satunya guru PAI di SLB X Kota Bandung yang juga merupakan individu dengan tunanetra (low vision). Guru yang tidak memiliki latar belakang pendidikan khusus biasanya memiliki pengetahuan teoritis dan praktis yang terbatas terkait ABK. Tujuan penelitian ini untuk mengetahui kompetensi yang dimiliki oleh guru PAI non PLB yang mengajar di SLB X Kota Bandung. Penelitian menggunakan metode kualitatif deskriptif, dengan alat pengumpulan data berupa wawancara, observasi, dan dokumentasi. Sumber data dalam penelitian ini berasal dari informan kunci yaitu wakil kepala sekolah SLB X bidang kurikulum, siswa SLB X, salah satu guru yang mengajar di SLB X, sedangkan informan inti yaitu guru PAI SLB X Kota Bandung. Berdasarkan hasil penelitian, meskipun guru PAI tidak berlatar belakang PLB, namun guru tetap bisa mengajar PAI pada ABK karena kondisi guru yang juga merupakan individu dengan tunanetra (low vision), kondisi pribadi ini turut mempengaruhi keberhasilan guru dalam mengajar karena guru dapat mengaplikasikan pengalaman dan pemahamannya kepada peserta didik yang menghadapi hambatan serupa. Namun, dalam hal teori-teori yang berkaitan dengan Pendidikan Luar Biasa (PLB) guru masih memiliki keterbatasan.